2013
DOI: 10.1603/en13043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Seasonal Variation in Bottom-Up and Top-Down Forces and Their Impact on an Exotic Wood Borer,Tetropium fuscum(Coleoptera: Cerambycidae)

Abstract: It is well understood that forces from multiple trophic levels simultaneously influence herbivore performance, but how the relative strength of these forces vary over space and time is less clear. We evaluated seasonal variation in the impact of bottom-up forces (host condition), top-down forces (natural enemies), and competition on the performance of an exotic wood borer. Tetropium fuscum (F.) (Coleoptera: Cerambycidae) eggs that were either protected or exposed were placed on healthy and stressed red spruce,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As larval development rate and survival of T. fuscum were also greater in girdled trees than in healthy trees (Flaherty et al . 2011, 2013a) the preference for girdled trees supported the preference–performance hypothesis (Jaenike 1978; Flaherty et al . 2013b).…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…As larval development rate and survival of T. fuscum were also greater in girdled trees than in healthy trees (Flaherty et al . 2011, 2013a) the preference for girdled trees supported the preference–performance hypothesis (Jaenike 1978; Flaherty et al . 2013b).…”
mentioning
confidence: 56%
“…Flaherty et al (2013b) showed that adult T. fuscum preferred to land on and lay more eggs on red spruce trees (Picea rubens Sargent) that had been moisture stressed by girdling compared with unmanipulated trees, and further showed that the beetles were more discriminating before they landed on the host than afterward. As larval development rate and survival of T. fuscum were also greater in girdled trees than in healthy trees (Flaherty et al 2011(Flaherty et al , 2013a) the preference for girdled trees supported the preference-performance hypothesis (Jaenike 1978;Flaherty et al 2013b).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…This regional difference has also been reported in other cerambycids in Japan [ 10 , 11 ]. Moreover, seasonal prevalence in a region has been reported to vary annually [ 12 , 13 ]. Considering this expected variation, a multi-year and multi-site survey in a region can help to identify a general trend of seasonal prevalence in the region; however, such surveys have rarely been conducted for A. bungii adults.…”
Section: Introductionmentioning
confidence: 99%